2006
DOI: 10.1111/j.1600-0722.2006.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental and medical injections: prevalence of self‐reported problems among 18‐yr‐old subjects in Norway

Abstract: The aim of the present study was to evaluate the prevalence of self-reported problems (fear, pain, unpleasantness, fainting) of dental and medical injections, and the extent to which such problems may lead to avoidance of necessary treatment. The study included a representative sample (n = 1385) of 18-yr-old students attending high schools in the county of Hordaland, Norway. Data were collected by use of questionnaires completed in the classrooms. More problems were reported during dental than medical injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 27 publications
(44 reference statements)
2
26
0
7
Order By: Relevance
“…reported the incidence of what they called common fears of injections to be about 13% among 10‐ and 20‐year‐olds. In a previous study among adolescents in Norway, we found that the prevalence of self‐reports of fainting and almost fainting during a dental or medical injection was 17% in this age group 13 . The facts that the prevalence of BIIP is estimated to be higher among children and adolescents compared to adults 5 , and that there is an overlap with DA, indicate that more knowledge is needed in this area of paediatric dentistry.…”
mentioning
confidence: 78%
“…reported the incidence of what they called common fears of injections to be about 13% among 10‐ and 20‐year‐olds. In a previous study among adolescents in Norway, we found that the prevalence of self‐reports of fainting and almost fainting during a dental or medical injection was 17% in this age group 13 . The facts that the prevalence of BIIP is estimated to be higher among children and adolescents compared to adults 5 , and that there is an overlap with DA, indicate that more knowledge is needed in this area of paediatric dentistry.…”
mentioning
confidence: 78%
“…The sample consisted of 1385 participants (770 girls) drawn as a random cluster sample (high schools) from a population of 18‐year‐old adolescents attending high schools in the county of Hordaland in Norway. The data were collected by use of questionnaires completed in the classroom as part of a larger survey, with a response rate of 99.7% 20 . The study was approved by the National Committees for Research Ethics in Norway.…”
Section: Methodsmentioning
confidence: 99%
“…1 Although third molar extraction also forms an excellent model of pain for testing analgesic effects, 2 this always concerns postoperative pain in which anxiety (as an anticipatory process) may be less relevant. Second, dental injections are an important aspect of dental treatment (at least in the perception of patients) which can induce dental anxiety or fear in children 3 and forms a source of distress or a compelling reason to avoid dental treatment altogether 4,5 in adults. So, dental injections provide a painful stimulus as well as a reason for anxiety and are provided at that point in time where anxiety may be hypothesized to be at its maximum for the patients.…”
Section: Introductionmentioning
confidence: 99%